Energy and Bandwidth-Efficient Wireless Transmission - Gao, Wei (Signals and Communication Technology,, 2017)
This book introduces key modulation and predistortion techniques for approaching energy and spectrum-efficient transmission for wireless communication systems. The book presents a combination of theoretical principles, practical implementations, and actual tests. It focuses on spectrum-efficient modulation and energy-efficient transmission techniques in the portable wireless communication systems, and introduces currently developed and designed RF transceivers in the latest wireless markets. Most materials, design examples, and design strategies used are based on the author's two decades of work in the digital communication fields, especially in the areas of the digital modulations, demodulations, digital signal processing, and linearization of power amplifiers. The applications of these practical products and equipment cover the satellite communications on earth station systems, microwave communication systems, 2G GSM and 3G WCDMA mobile communication systems, and 802.11 WLAN systems.